Antimicrobial Efficacy of Biogenic Manganese Oxide Nanoparticles Against Klebsiella pneumonia: A Novel Approach to Combat Antibiotic Resistance - Noman, Muhammad; Ghazal, Areesa; Ali, Akbar; Yameen, Qaria; Naqvi, Syeda Taseer Zahra; Bibi, Aasia; Mushtaq, Novera; Younas, Hafiza Sania (Biological and Clinical Sciences Research Journal, 2025)
The rise of multidrug-resistant (MDR) bacteria has emerged as a critical global health concern, significantly impeding effective infection management. Conventional antibiotics are increasingly failing against pathogens such as Klebsiella pneumoniae, which is notorious for its resistance and prevalence in nosocomial infections. This has necessitated the exploration of alternative antimicrobial strategies. Objective: To evaluate the antibacterial, antibiofilm, and cytotoxic effects of biogenically synthesized manganese oxide nanoparticles (MnO NPs) against multidrug-resistant Klebsiella pneumoniae. Methods: This experimental study involved the biosynthesis of manganese oxide nanoparticles followed by their evaluation against Klebsiella pneumoniae. Antibacterial activity was assessed using the agar well diffusion assay. Minimum inhibitory concentration (MIC) was determined via the broth dilution method. Antibiofilm activity was quantified using the crystal violet microtiter plate assay. The effect of sub-inhibitory concentrations of MnO NPs on extracellular polymeric substances (EPS) was also studied. Cytotoxicity was evaluated using the neutral red uptake assay and morphological analysis of HepG2 human liver cell lines. Results: Manganese oxide nanoparticles demonstrated notable antibacterial activity with clear zones of inhibition in agar diffusion assays. MIC testing revealed significant growth inhibition of K. pneumoniae at defined nanoparticle concentrations. MnO NPs also significantly reduced biofilm formation and disrupted EPS production at sub-MIC levels. Cytotoxicity assays indicated that MnO NPs exhibited minimal toxic effects on HepG2 cells at effective antimicrobial concentrations, suggesting good biocompatibility. Conclusion: Biogenically synthesized manganese oxide nanoparticles possess potent antibacterial and antibiofilm activity against Klebsiella pneumoniae, with minimal cytotoxicity to human liver cells. These findings suggest that MnO NPs may offer a promising alternative therapeutic approach to combat multidrug-resistant bacterial infections.